Swedish snus and the GothiaTek® standard - Ringberger Tommy; Hassler Thord; Curvall Margareta; Rutqvist Lars E; Wahlberg Inger (BMC, 2011)
Abstract Some smokeless tobacco products, such as Swedish snus, are today considered to be associated with substantially fewer health hazards than cigarettes. This risk differential has contributed to the scientific debate about the possibilities of harm reduction within the tobacco area. Although current manufacturing methods for snus build on those that were introduced more than a century ago, the low levels of unwanted substances in modern Swedish snus are largely due to improvements in production techniques and selection of raw materials in combination with several programs for quality assurance and quality control. These measures have been successively introduced during the past 30-40 years. In the late 1990s they formed the basis for a voluntary quality standard for Swedish snus named GothiaTek®. In recent years the standard has been accepted by the members of the trade organization European Smokeless Tobacco Council (ESTOC) so it has now evolved into an industrial standard for all smokeless tobacco products in Europe. The initial impetus for the mentioned changes of the production was quality problems related to microbial activity and formation of ammonia and nitrite in the finished products. Other contributing factors were that snus came under the jurisdiction of the Swedish Food Act in 1971, and concerns that emerged in the 1960s and 1970s about health effects of tobacco, and the significance of agrochemical residues and other potential toxicants in food stuffs. This paper summarizes the historical development of the manufacture of Swedish snus, describes the chemical composition of modern snus, and gives the background and rationale for the GothiaTek® standard, including the selection of constituents for which the standard sets limits. The paper also discusses the potential future of this voluntary standard in relation to current discussions about tobacco harm reduction and regulatory science in tobacco control.